Association of Diabetes Mellitus and Histopathological Diagnosed Lichen Planus - Darad, Dimple; Chauhan, Savitri (Annals of Pathology and Laboratory Medicine, 2018)
Background and Aim: It is reported, that the presence of lichen planus among diabetic patients and the presence of diabetes in patients who are suffering from oral lichen planus has a correlation. Diabetes is being treated with antidiabetic drugs and certain antidiabetic drugs can cause an allergic manifestation to produce lichenoid reaction. Hence the present aim of study was to find out the prevalence of lichen planus among diabetic patient. Materials & Methods: Present study was carried out at a department of pathology GMERS Medical College, Gotri, Vadodara, Gujarat. All the participants did underwent the history, general and systemic examination which was followed by biochemical investigation for the blood sugar that is estimation of fasting blood sugar. Detailed history with clinical and dermatological examination was done. Fasting blood sugar was analysed. Skin biopsy was being taken from the skin lesion site and its histopathological examination was being done. Results: On the basis of the biochemical analysis for diabetes, out of 100 patients included in the study, 49 were confirmed with the presence of diabetes. All the patients confirmed with diabetes were in type II diabetic patients, none of them were diagnosed with type I diabetes. There was significant relation between the presence of lichen planus and type II diabetes with p valus < 0.05. Conclusion: Lichen planus is a disease of adults (20–40 years) according to western data (Andreason, 1968; Scully, 1985) but in Indian population it is also common in the paediatric age group. The excess sugar in diabetes may not be a cause for lichen planus as nondiabetic patients also develops lichen planus, anxiety and stress seems to be associated with diabetes and this may be a reason precipitating lichen planus in diabetic patients. DOI:10.21276/APALM.1923